The effect of dependence on distribution of the functions of random variables. Issue 21 (2nd November 2017) - Dolati, Ali; Roozegar, Rasool; Ahmadi, Najmeh; Shishebor, Zohreh
ABSTRACT: In this article, we study the effect of dependence on the distributional properties of functions of two random variables. Expressions for the cumulative distribution functions of the linear combinations, products, and ratios of two dependent random variables in terms of their associated copula are derived. We discuss the effect of dependence on quantities such as the variances of linear combinations of functions, the value-at-risk measure, and the stress–strength parameter. Several examples, a simulation study, and a real data analysis are provided to illustrate the result.